Perbandingan Hasil Belajar Dengan Menggunakan Model Group Investigation dan Quantum Teaching Pada SMK Negeri 1 Lubuk Basung “Studi Kasus Pada Siswa Kelas X Akuntansi Mata Pelajaran Akuntansi Dasar” - Nika Dayani; Annur Fitri Hayati (Universitas Negeri Padang, 2019)
Comparison of student learning outcomes between learning using the Group Investigation Model and Quantum Teaching on Financial Report material. This study aims to determine the differences and improvement of student learning outcomes in the application of Group Investigation and Quantum Teaching in financial report material. The research design used was the Nonequivalent Control Design Group. In the first experimental class the average score of student learning outcomes was 80.95 and the increase in the average score of student learning outcomes was 47.57 with N-gain of 0.71 (high category). In the second experimental class the average score of student learning outcomes was 88.24 and the increase in the average score of student learning outcomes was 52.05 with N-gain of 0.81 (high category). The results of the study showed that there were differences in student learning outcomes between the experimental classes applying the Group Investigation and Quantum Teaching. These results indicate that the application of the Quantum Teaching model is higher for improving student learning outcomes.Keyword: group investigation, student learning outcomes, quantum teaching